2018
DOI: 10.1111/1742-6723.13127
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐hospital arrests attending an Australian tertiary paediatric emergency department over 13 years: An observational study

Abstract: Children presenting to ED still receiving cardiac compressions following OHCA had a universally poor outcome, regardless of age and underlying cause. This implies resuscitative efforts could be discontinued earlier in this subgroup. A national, multicentre study is needed to determine if this finding is reproducible with a larger population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 32 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…1 The authors found that none of the 60 paediatric patients survived and reasoned that prolonged pre-hospital CPR and delayed transport may be an important factor in the dismal survival rate. 1 The authors found that none of the 60 paediatric patients survived and reasoned that prolonged pre-hospital CPR and delayed transport may be an important factor in the dismal survival rate.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1 The authors found that none of the 60 paediatric patients survived and reasoned that prolonged pre-hospital CPR and delayed transport may be an important factor in the dismal survival rate. 1 The authors found that none of the 60 paediatric patients survived and reasoned that prolonged pre-hospital CPR and delayed transport may be an important factor in the dismal survival rate.…”
mentioning
confidence: 99%
“…1 Simply exhorting ambulance personnel 'to scoop up the child in arms, run to the ambulance, and drive as fast as possible to hospital' 2 may not lead to increased survival except in rare circumstances, such as hypothermia, drug overdose and in some cases of refractory ventricular fibrillation. 1 Simply exhorting ambulance personnel 'to scoop up the child in arms, run to the ambulance, and drive as fast as possible to hospital' 2 may not lead to increased survival except in rare circumstances, such as hypothermia, drug overdose and in some cases of refractory ventricular fibrillation.…”
mentioning
confidence: 99%
See 3 more Smart Citations